Experimental evidence for the boundary zonal flow in rotating Rayleigh–Bénard convection. (25th May 2022) - Wedi, Marcel; Moturi, Viswa M.; Funfschilling, Denis; Weiss, Stephan
Abstract: Abstract : We report on the presence of the boundary zonal flow in rotating Rayleigh–Bénard convection evidenced by two-dimensional particle image velocimetry . Experiments were conducted in a cylindrical cell of aspect ratio $\varGamma =D/H=1$ between its diameter ( $D$ ) and height ( $H$ ). As the working fluid, we used various mixtures of water and glycerol, leading to Prandtl numbers in the range $6.6 \lesssim Pr \lesssim 76$ . The horizontal velocity components were measured at a horizontal cross-section at half height. The Rayleigh numbers were in the range $10^8 ≤ Ra ≤ 3× 10^9$ . The effect of rotation is quantified by the Ekman number, which was in the range $1.5× 10^{-5}≤ Ek ≤ 1.2× 10^{-3}$ in our experiment. With our results we show the first direct measurements of the boundary zonal flow (BZF) that develops near the sidewall and was discovered recently in numerical simulations as well as in sparse and localized temperature measurements. We analyse the thickness $δ _0$ of the BZF as well as its maximal velocity as a function of Pr, Ra and Ek, and compare these results with previous results from direct numerical simulations.